AN ERROR ANALYSIS OF SEMANTIC LEVEL IN RIAU NEWSPAPER ARTICLES: ANALISIS KESALAHAN BERBAHASA TATARAN SEMANTIK DALAM ARTIKEL SURAT KABAR KORAN RIAU - Alber Alber; Hermaliza Hermaliza (LLDIKTI Wilayah X, 2021)
Language errors often occur when communicating, both oral communication and written communication. This happens because of the lack of understanding of the communicator in delivering messages to the communicant or the author's lack of understanding in providing information to his readers. In addition, language errors also often occur due to spoken language factors, so that when applied in written language, there tend to be errors. Language errors at the semantic level still often occur in written language, especially articles in the Riau newspaper. These errors can be in the form of errors due to confused pairs, errors due to incorrect choice of words, and errors due to cognate pairs. This study uses a prescriptive content analysis method with the data source from the newspaper Koran Riau. Data is collected by means of documentation with data collection techniques including, collecting error samples, identifying errors, explaining errors, classifying errors, and evaluating or correcting errors. Based on the results and discussion, there are two errors in the language of the semantic level in the Riau Koran newspaper article. First, the fault of a confused partner. Second, errors due to incorrect word choices. However, errors due to cognate pairs were not found.